MATHEMATICAL MODELING OF UNSTEADY HEAT EXCHANGE IN A PASSENGER CAR - I. Yu. Khomenko (Nauka ta progres transportu, 2013)
Purpose.Existing mathematicalmodelsofunsteadyheatexchangeinapassengercardonotsatisfytheneedofthedifferentconstructivedecisionsofthelifesupportsystemefficiencyestimation. They also don’t allow comparing new and old life support system constructions influence on the inner environment conditions. Moreoverquite frequently unsteady heat exchange processes were studied at the initial car motion stage. Due to the new competitive engineering decisionsof the lifesupportsystemthe need of a new mathematical instrument that would satisfy the mentioned features and their influence on the unsteadyheatexchangeprocesses during the whole time of the road appeared. The purpose of this work is creation of the mathematicalmodel ofunsteadyheatexchangeinapassengercarthatcan satisfythe above-listed requirements. Methodology. Fortheassigned task realizationsystemofdifferentialequationsthatcharacterizesunsteadyheatexchangeprocessesinapassengercarwascomposed; forthesystemof equationssolution elementary balance method was used. Findings. Computational algorithm was developed andcomputer program for modeling transitional heat processes in the car was designed. It allows comparing different life support system constructions influence on the inner environment conditionsand unsteady heat exchange processes can be studied at every car motion stage. Originality.Mathematicalmodelofunsteadyheatexchangeinapassengercarwasimproved. That is why it can be used for the heat engineering studying of the inner car state under various conditions and for the operation of the different life support systems of passenger cars comparison. Mathematicalmodelingofunsteadyheatexchangeinapassengercarwas made by the elementary balance method. Practical value. Created mathematical model gives the possibility to simulate temperature changes in passenger car on unsteady thermal conditions with enough accuracy and to introduce and remove additional elements to the designed model. Thus different constructive decisions of the life support system can be estimated by the mathematical experiment.